'…a one stop shop in their own community': Medical abortion and the role of general practice. (21st July 2016) - Newton, Danielle; Bayly, Chris; McNamee, Kathleen; Bismark, Marie; Hardiman, Annarella; Webster, Amy; Keogh, Louise
Abstract : Background: The introduction to Australia of modern medical abortion methods, which require less specialist expertise and equipment than the more traditional surgical methods, have brought an as yet unrealised potential to improve access to abortion services. Aims: To investigate the potential for expanding the role of general practice in the provision of medical abortion in Victoria. Materials and methods: In 2015, in‐depth interviews were conducted with 19 experts in abortion service provision in Victoria. A semi‐structured interview schedule was used to guide the interviews. Interviews were transcribed verbatim and transcripts analysed thematically. Results: Participants were largely very supportive of the provision of early medical abortion in general practice as a way of increasing abortion access for women, particularly in rural and regional communities. Access to abortion was seen as an essential component of women's comprehensive health care and therefore general practitioners (GPs) were perceived as ideally placed to provide this service. However, this would require development and implementation of new service models, careful consideration of GP and nurse roles, strengthening of partnerships with other health professionals and services in the community, and enhanced training, support and mentoring for clinicians. Conclusion: The application of these findings by relevant health services and agencies has the potential to increase provision of medical abortion services in general practice settings, better meeting the health‐care needs of women seeking this service.